THAI STUDENTS' DEVIATION IN ENGLISH PRONUNCIATION - Natlada Makamthong; Vega Hesmatantya (ELLTER Journal, 2022)
When Thai students spoke English, they frequently deviated from the English consonant sounds. This aspect significantly influences the level of misunderstanding in English communication. This study aims to look at the variables that cause Thai students to deviate from English consonant sounds and the many phonological issues that cause Thai students to deviate from English sounds. The research approach employed in this study was descriptive qualitative. The participants in this study were twelve Thai students from Universitas Muhammadiyah Surabaya. The data was examined using PRAAT, which was used to record and transcribe the participants' conversations. This study demonstrates that respondents' deviation of English sounds differs significantly. Their phonological difficulty was aided by many circumstances, resulting in a variation in English consonant sounds.